Postherpetic Neuralgia Induced Asystole - A Deadly Consequence of a Common Disease - Mohan, Ayesha; Hoque, Farzana (Journal of Medicine, 2023)
Postherpetic neuralgia is a well-studied and somewhat common sequala of herpes zoster leading to intense pain episodes. Pain-induced vasovagal episodes can rarely lead to asystole, which is a fatal potential complication. It is crucial to have a high clinical suspicion of asystole when a patient presents with severe herpetic neuralgia leading to syncope. This is a unique cause of a 67-year-old Caucasian female who presented with syncope caused by severe postherpetic neuralgia with the eventual finding of pain-induced asystole episodes. J MEDICINE 2023; 24(2): 162-165